Porches & outdoor spaces (Hearts Books, 2015)
Whether for a porch, patio, deck, sunroom, or garden; and whether the style is classic, rustic, retro, or flea-market funky, there are plenty of ideas here for you. Get timeless good looks on a budget, revamp with paint and simple furnishings, bring interiors outside, and incorporate charmingly traditional elements like farm-stand tables, wooden gliders, swings, and white wicker. Whether you're ready to tackle a major project or just want a couple of quick, easy ideas, this is the perfect, beautiful book for you.